Chikungunya Arthritis Mechanisms in the Americas: A Cross‐Sectional Analysis of Chikungunya Arthritis Patients Twenty‐Two Months After Infection Demonstrating No Detectable Viral Persistence in Synovial Fluid. Issue 4 (7th March 2018) - Chang, Aileen Y.; Martins, Karen A. O.; Encinales, Liliana; Reid, St. Patrick; Acuña, Marlon; Encinales, Carlos; Matranga, Christian B.; Pacheco, Nelly; Cure, Carlos; Shukla, Bhavarth; Ruiz Arteta, Teofilo; Amdur, Richard; et al.
Abstract : Objective: To determine if chikungunya virus persists in synovial fluid after infection, potentially acting as a causative mechanism of persistent arthritis. Methods: We conducted a cross‐sectional study of 38 Colombian participants with clinical chikungunya virus infection during the 2014–2015 epidemic who reported chronic arthritis and 10 location‐matched controls without chikungunya virus or arthritis. Prior chikungunya virus infection status was serologically confirmed, and the presence of synovial fluid chikungunya virus, viral RNA, and viral proteins was determined by viral culture, quantitative reverse transcription–polymerase chain reaction (qRT‐PCR), and mass spectrometry, respectively. Biomarkers were assessed by multiplex analysis. Results: Patients with serologically confirmed chikungunya arthritis (33 of 38 [87%]) were predominantly female (82%) and African Colombian (55%) or white Colombian (33%), with moderate disease activity (mean ± SD Disease Activity Score in 28 joints 4.52 ± 0.77) a median of 22 months after infection (interquartile range 21–23 months). Initial symptoms of chikungunya virus infection included joint pain (97%), swelling (97%), stiffness (91%), and fever (91%). The most commonly affected joints were the knees (87%), elbows (76%), wrists (75%), ankles (56%), fingers (56%), and toes (56%). Synovial fluid samples from all patients with chikungunya arthritis were negative for chikungunya virus on qRT‐PCR, showed no viral proteins on mass spectrometry, and cultures were negative. Case and control plasma cytokine and chemokine concentrations did not differ significantly. Conclusion: This is one of the largest observational studies involving analysis of the synovial fluid of chikungunya arthritis patients. Synovial fluid analysis revealed no detectable chikungunya virus. This finding suggests that chikungunya virus may cause arthritis through induction of potential host autoimmunity, suggesting a role for immunomodulating agents in the treatment of chikungunya arthritis, or that low‐level viral persistence exists in synovial tissue only and is undetectable in synovial fluid.